Comparison between two methods for determination of mechanical power in vertical jumping - doi: 10.4025/reveducfis.v23i2.15018 - Storniolo, Jorge Luiz; Fischer, Gabriela; Tartaruga, Leonardo Alexandre (Journal of Physical Education (Maringá), 2012)
The aim of this study was to compare the mechanical power values of vertical jumps measured by BOSCO test (Theoretical Power, PT) with mechanical power values registered by force plate (Experimen Power, PE) and verify the agreement between the two methods. Eleven recreational runners performed continuous maximal jumps for 60 seconds. Force platform 3D and 2D kinematics system were used for calculation of PT and PE, respectively. Data about flight time and number of hops were obtained from the kinematic analysis (Dvideow 5.0). We used Bland & Altman for agreement between the methods. The average values of PT and PE were 15.6 ±2.4 W.kg-1 and 20.8 ±3.2 W.kg-1, respectively, ranging from the agreement limits ±2 s.d. Therefore, the equation of the PT is a convenient method for determining the mechanical power during continuous vertical jumps.